ALTERATION IN DISPOSITION KINETICS OF WARFARIN MEDIATED BY CAFFEINE IN HEALTHY MALE ALBINO RABBITS - S. Zafar; A. Ali; M. M. Ashraf; 3; J. A. Khan; B. Aslam; R. D. Naseer (Journal of Animal and Plant Sciences, 2019)
Many physicians are afraid of being involved in allegation of malpractices due to occurrence of severe drug interactions. These interactions not only occur between drugs but also between any kind of food, tobacco smoke, caffeine and alcohol etc. Therefore, current study was conducted to inspect the effect of caffeine on the disposition kinetics of warfarin in ten healthy adult male albino rabbits. Blood samples were collected at same time intervals after administration of warfarin (0.5 mg.kg-1) alone and then in its combination with caffeine (5 mg.kg-1 every twelve hours for three days) following a washout period of 14 days in each rabbit. Warfarin concentration in plasma was measured by high performance liquid chromatographic (HPLC) technique to determine pharmacokinetic parameters. Paired t-test was applied on data for its statistical comparison. Plasma concentration values of warfarin enhanced significantly at each time interval after its co-administration with caffeine. Significant increase was observed in Kabs (from 0.4±0.0 hr-1 to 0.5±0.0 hr-1), t1/2β (from 34.1±4.8 hr to 49.1±2.4 hr), AUC (from 109.3±10.6 µg.h.mL-1 to 147.2±6.4 µg.h.mL-1) and MRT (from 52.1±6.7 hr to 72.9±3.4 hr) of warfarin after its concomitant administration with caffeine. Whereas, a significant decrease in t1/2abs (from 2.0±0.2 hr to 1.5±0.1 hr), β (from 0.03±0.0 hr-1 to 0.01±0.0 hr-1) and ClB (from 0.01±0.0 L.hr-1kg-1 to 0.004±0.0 L.hr-1kg-1) of warfarin was observed after its combination with caffeine. Caffeine slows down the biotransformation of warfarin resulting in reduced elimination of warfarin which leads to increased concentration of warfarin within the body. Thus, anticoagulant activity of warfarin may enhance in combination with caffeine. So, clinicians should avoid or be cautious while using caffeine during warfarin therapy to avoid any mishap or unwanted event.
Keywords: Pharmacokinetics; Anticoagulant; Interaction; Metabolism